Quo Vadis Gerotranscendence?: A Systematic Literature Network Analysis of Existing Themes and Emerging Trends in Gerotranscendence Theory with a Focus on International Applications - Pamuk, Deniz (Journal of religion and health, 2025)
Lars Tornstam's Gerotranscendence Theory suggests that the aging process involves a shift in perspective from materialistic concerns to a more cosmic outlook, characterized by transcendence in cosmic, personal, and social dimensions. This study uses a Systematic Literature Network Analysis to explore the central themes and emerging trends in gerotranscendence-related research. A total of 139 articles published between 1992 and 2024 were retrieved from the ISI Web of Science database. The findings revealed core thematic areas including aging care, religiosity, and reminiscence, along with emerging areas such as marketing, environmental design, and gerontology. Although the theory originated in Sweden, its application has become increasingly global, with significant research in countries such as India, China, and Turkey. Despite its relatively recent development, gerotranscendence demonstrates considerable potential as a conceptual framework for interventions that promote positive aging.